POTRET KEWIRAUSAHAAN PENGRAJIN SOUVENIR DARI OLAHAN TEMPURUNG KELAPA DI DESA KARANGTENGAH KECAMATAN BATURRADEN KABUPATEN BANYUMAS - Gilang Septian Tegar Permana; Dumasari Dumasari; Pujiharto Pujiharto (Universitas Muhammadiyah Purwokerto, 2015)
This research aimed to know a portrait of entrepreneurship craftsmen souvenirs from processed coconut shell in Karangtengah Village, Subdistrict Baturraden, Banyumas Regency related to some aspect that was pre-production, production process and post production. That data was used primary and secondary data. Sample taken used purposive sampling technique. The survey results revealed that the portrait of entrepreneurial farmers artisans souvenirs from coconut shell related aspects of pre-production include: Provision of raw materials, equipment, provision of workshops and capital. A portrait of entrepreneurship craftsmen souvenirs from precessed coconut shell related post-production aspect include: craftsmen 100% in post-production did not the packing technique. Marketing outlets of souvenirs craft that direct and indirect. Constraint problems that done was the lower prices because many of the competition, a less extensive marketing coverage, the consumerdoes not have deserted so wide.